Geometric tools for computer graphics - Schneider, Philip J.; Eberly, David H. (Amsterdam : Morgan Kaufmann Publishers, 2003)
Do you spend too much time creating the building blocks of your graphics applications or finding and correcting errors? Geometric Tools for Computer Graphics is an extensive, conveniently organized collection of proven solutions to fundamental problems that you'd rather not solve over and over again, including building primitives, distance calculation, approximation, containment, decomposition, intersection determination, separation, and more. If you have a mathematics degree, this book will save you time and trouble. If you don't, it will help you achieve things you may feel are out of your reach. Inside, each problem is clearly stated and diagrammed, and the fully detailed solutions are presented in easy-to-understand pseudocode. You also get the mathematics and geometry background needed to make optimal use of the solutions, as well as an abundance of reference material contained in a series of appendices. * Filled with robust, thoroughly tested solutions that will save you time and help you avoid costly errors. * Covers problems relevant for both 2D and 3D graphics programming. * Presents each problem and solution in stand-alone form allowing you the option of reading only those entries that matter to you. * Provides the math and geometry background you need to understand the solutions and put them to work. * Clearly diagrams each problem and presents solutions in easy-to-understand pseudocode. * Resources associated with the book are available at the companion Web site www.mkp.com/gtcg.
Preface -- 1. Introduction -- 2. Matrices and Linear Systems -- 3. Vector Algebra -- 4. Matrices, Vector Algebra, and Transformations -- 5. Geometric Primitives in 2D -- 6. Distance in 2D -- 7. Intersection in 2D -- 8. Miscellaneous 2D Problems -- 9. Geometric Primitives in 3D -- 10. Distance in 3D -- 11. Intersection in 3D -- 12. Miscellaneous 3D Problems -- 13. Computational Geometry Topics -- A. Numerical Methods -- B. Trigonometry -- C. Basic Formulas For Geometric Primitives -- Bibliography.
Διαθέσιμο και σε ηλεκτρονικό βιβλίο, τρόπος πρόσβασης μέσω διαδικτύου.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Computer graphics; Geometry -- Data processing; Three-dimensional display systems; Electronic books